Dashboard-Based Distribution Requirements Planning for Reverse Logistics Scheduling Optimization in Community Waste Collection - Nia Novitasari; Gisti Ayu Pratiwi (RAM PUBLISHER, 2026)
This study aims to develop a dashboard-based waste collection scheduling system using the Distribution Requirements Planning (DRP) approach to improve the effectiveness of sorted gallon waste collection at Bank Sampah Bersinar (BSB), Bojongsoang. BSB manages six recycle points with a total weekly collection demand of 4,050 kg, while the available fleet consists of only one pick-up vehicle with a capacity of 1,000 kg. The absence of a structured collection schedule previously caused simultaneous collection activities and potential over-dimension and over-load problems. This study applies DRP to allocate collection activities based on demand volume, fleet capacity, operational time, and BSB’s three-day collection policy. The result shows that all weekly waste volume can be collected within three operational days by visiting two recycle points per day, with two trips conducted each day. In addition, a monitoring dashboard was developed to support daily trip tracking, collection volume monitoring, and recycle point performance evaluation. The proposed system provides a practical solution for improving reverse logistics operations, reducing fleet overload risk, and supporting data-based decision-making in community waste management.